Budowanie związków uczuciowych z wykorzystaniem sieci internetowej – studium pedagogiczne - Dodge, Brygida (Neodidagmata, 2018)
Emotional relationships on the Internet is a topic that still causes quite a big surprise – In particular among generations that did not grow up surrounded by the Internet. Very often, it also evokes extreme emotions from these people, for example by diminishing the nature of a relationship that would supposedly be inauthentic. These factors became a reason for doing research on the issue of building emotional relationships using the Internet, the purpose of which was to explore the possibility of creating such a relationship. This article presents – in theoretical and practical aspects – the areas of the Internet as a place for establishing emotional relations, methods of online communication, theoretical approach to loving relationships and even psychological concepts describing the possibilities of building relationships on the network. Selected dating websites and their characteristics were also presented. In the final part, the methods and results of research on the possibility of building relationships on the Internet and the conclusions drawn from the evidence.